Stress, Coping Style and Nursing Needs for Hospitalized Pregnant Women due to Preterm Labor - Su Hyun Kim; Hyang In Cho Chung (Korean Society of Women Health Nursing, 2015)
PURPOSE: The purpose of this descriptive study was to assess levels of stress, coping style, and nursing needs for hospitalized pregnant women diagnosed with preterm labor. METHODS: Data were collected from 125 pregnant women aged between 20 and 40 years and diagnosed with preterm labor by OBGY units at 3 hospitals. Data were analyzed by frequency, percentage, t-test, and ANOVA with Scheffe test. RESULTS: The level of stress among women was an average of 2.13 out of 4 points, the level of coping style was an average of 2.66, and nursing needs was an average of 2.83 out of 4 points. The level of stress was significantly different by job, length of hospital stay, type of hospital, and history of admission at obstetric unit. The level of coping style was significantly different by age and monthly income. The level of nursing needs was significantly different by type of hospital. Higher level of stress and coping style were related to higher level of nursing needs. There was no significant correlation between stress and coping style. CONCLUSION: The result showed the importance of nursing intervention dealing with stress, coping style and nursing needs for women with preterm labor. Nurses need to provide nursing interventions to reduce the stress, to strengthen the coping style, and to satisfy the nursing needs for pregnant women hospitalized due to preterm labor.